Revisiting the evolution of non-geniculate coralline algae taxonomy: History and perspectives - Leão, Luis A.S.; Bahia, Ricardo da G.; Karez, Cláudia S.; Salgado, Leonarado T.; Pereira, Renato C. (Aquatic botany, 2024)
Non-geniculate coralline algae (NGCA), Corallinophycidae - Rhodophyta, are characterized by prominent calcified vegetative thalli. They exhibit broad phenotypic plasticity, and morphoanatomical convergences due to the simplicity of their thalli. These characteristics makes their taxonomy one of the most complex within Rhodophyta. The nomenclature and taxonomy of the NGCA have been controversial and subject to intensive debate even after the advent of molecular techniques. Until the mid-19th century, all calcareous organisms were classified as animals. Still, the algal nature of the NCG became evident with advances in microscopy and anatomical techniques, based on anatomical and reproductive attributes rather than thallus form. This review provides a comprehensive historical overview of significant milestones in the NGCA taxonomy. From 1890–1910, Mikael Foslie described about 400 species of NGCA. Since then, and after the advances in microscopy in the mid-20th century, the taxonomy of this algal group, traditionally based on morphological aspects, has been replaced by anatomical features. Paraffin and historesin-embedded microtomy and sectioning techniques allowed access to taxonomically relevant microanatomical features, while scanning and transmission electron microscopy allowed access to ultrastructural aspects. The subsequent use of molecular markers promoted a real revolution, by disclosing phylogenetic relationships between taxa. As perspectives, high-resolution confocal microscopy images can provide information on intricate three-dimensional structures and reveal unexplored aspects of NGCA morphoanatomy. Meanwhile, whole-genome sequencing and comparative genomics can uncover the genetic underpinnings of taxonomic variations, helping to elucidate the mechanisms driving the diversification of NGCA species. We envision that the recent expansion of sampling expeditions to previously unknown geographic and bathymetric regions along with the convergence of advanced morphoanatomy imaging, genomics, and bioinformatics, would clarify the complex tapestry of NGCA taxonomy and safeguard (e.g., through conservation action-plans) these ecologically important marine organisms. •Rhodolith are marine nodule with species of non-geniculate coralline algae (NGCA).•Historically, the identification of NGCA has been and still is a very complex task.•We provide a historical review about the controversial development of taxonomy of NGCA.•NGCA taxonomy needs to use imaging, genomics, bioinformatics and their distribution.